2005
DOI: 10.1135/cccc20050085
|View full text |Cite
|
Sign up to set email alerts
|

A Regioselective Synthesis of Alkyl 2-(Guanin-9-yl)acetates as PNA Building Blocks from 7-(4-Nitrobenzyl)guanine Derivatives

Abstract: Guanine derivatives substituted at N7 with 4-R-benzyl groups (R = H, MeO, NO2) have been evaluated in the regioselective N9-alkylation of guanine. Given the capricious removal of (substituted) benzyl groups from guanine derivatives and pent-4-enoylation of guaninium hydrochloride, an improved alternative approach has been elaborated consisting in the pent-4-enoylation and per-O-acetylation of guanosine (8), 4-nitrobenzylation at N7 followed by N-glycoside hydrolysis (10), N9-alkylation (13) and deprotection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 56 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…[173] Sodium sulfide is known to be used for the removal of PNB group, but in the case of imidazolium 258 hydroxyl mediated ring opening occurred instead of protecting group removal and the PNB protected FAPY 259 was obtained (Scheme 43). [174] FAPY fragments are also found in natural products, for example, agelasines 260 a-c are bioactive purine derivatives with terpene side chain found in marine sponges of genus Agelas. They are associated with antimicrobial bioactivity and cytotoxic effects in cells.…”
Section: Ring Opening Of the Imidazole Moiety In Purines 31 Ring Open...mentioning
confidence: 99%
See 1 more Smart Citation
“…[173] Sodium sulfide is known to be used for the removal of PNB group, but in the case of imidazolium 258 hydroxyl mediated ring opening occurred instead of protecting group removal and the PNB protected FAPY 259 was obtained (Scheme 43). [174] FAPY fragments are also found in natural products, for example, agelasines 260 a-c are bioactive purine derivatives with terpene side chain found in marine sponges of genus Agelas. They are associated with antimicrobial bioactivity and cytotoxic effects in cells.…”
Section: Ring Opening Of the Imidazole Moiety In Purines 31 Ring Open...mentioning
confidence: 99%
“…Sodium sulfide is known to be used for the removal of PNB group, but in the case of imidazolium 258 hydroxyl mediated ring opening occurred instead of protecting group removal and the PNB protected FAPY 259 was obtained (Scheme 43). [174] …”
Section: Ring Opening Of the Imidazole Moiety In Purinesmentioning
confidence: 99%
“…( N 2 ‐Acyl‐guanin‐9‐yl)acetic esters 1 (9IbuMe), 3 (9IbutBu)4 and 5 (9PnttBu)14 have been synthesized in our laboratory as PNA monomer building blocks and studied by electrospray ionization tandem mass spectrometry (ESI‐MS/MS) along with their N 7 ‐regioisomer pairs 2 (7IbuMe) and 4 (7IbutBu), respectively4 (Fig. 1).…”
Section: Structures Of Alkylated Guanine Derivatives Studied By Ms/msmentioning
confidence: 99%
“… The statistical analysis of 13 C NMR chemical shift parameters of over 50 compounds [3,16] revealed that guanine's δ C−5 is the most sensitive to the N 9 / N 7 substitution pattern (for the compounds studied δ C−5 (N‐9): 113.75–123.70 ppm; δ C−5 (N‐7): 104.56–115.09 ppm). However, due to the overlapping of chemical shift ranges for regioisomers (especially for glycosides) this chemical shift alone might not be sufficient for unambiguous assignment.…”
Section: Peptide Nucleic Acidsmentioning
confidence: 99%
“…En route to PNA oligomers, the difficulties accompanying the regioselective alkylation of guanine derivatives prompted us to continue our efforts towards elaborating a synthetic method to solve this vexing problem [16] …”
Section: Peptide Nucleic Acidsmentioning
confidence: 99%